Tratamento de efluente contendo tiametoxan e avaliação da sua eficiência na redução da toxicidade - Fieira, Clarice (2019)
The treatment of seeds with agrochemicals is a technique widely used by companies and farmers in pre-planting. This is done through specific machines and equipment that, at the end of the process, need to be cleaned, producing contaminated effluents. The objective of the study was to characterize and evaluate the effluent toxicity of the washing of seed treatment machines, containing the thiamethoxan agrochemical as active principle, suggesting easy and low cost treatment methods. In the adsorption effluent treatments, using activated charcoal, corn straw and soybean hull, varying pH and mass concentration of each material, a better reduction was observed in the chemical oxygen demand (COD) with activated charcoal, followed by corn straw n the treatment by coagulation/flocculation, with ferric chloride (FeCl3) and aluminum polychloride, using a factorial design, having as independent variables the FeCl3 concentration and the sedimentation time, the test that obtained the best COD removal was with the concentration of 850 mg L-1 of FeCl3 and 120 min of sedimentation. From the preliminary results, the following final treatments were chosen: ACA (adsorption with activated charcoal at natural pH (8) with 6 g L-1), APM (adsorption with corn straw at natural pH (8) with 6 g L-1), C (coagulation and flocculation with 850 mg L-1 of FeCl3 and sedimentation time of 120 min); CCA (coagulation and flocculation with subsequent adsorption with activated charcoal) and CPM (coagulation and flocculation with subsequent adsorption with corn straw). The treatments C, CCA and CPM presented the best removals of physico-chemical parameters (pH, COD, chemical oxygen demand, oils and greases, dissolved solids and total solids). The best removals of the active thiamethoxanwere observed in the CCA treatments, followed by the CPM. In general, however, all groups (gross and treated effluents) showed high toxicity to the bioindicators Artemia salina L. (immobility / mortality test), Eisenia fetida (leak test) and Allium cepa L. (cytotoxicity test). A mutagenic effect was also observed for A. cepa, due to the presence of chromosomal alterations in the groups evaluated. The results indicate the risk that this effluent presents to the environment, observing the need for investigations of new technologies of treatment of this effluent, in order to facilitate the reduction of the physical-chemical parameters, the agrochemical and, in particular, the final toxicity of the effluent.